PENGARUH KEPUASAN KERJA, PENGEMBANGAN KARIR, DAN LINGKUNGAN KERJA TERHADAP TURNOVER INTENTION DI PT XYZ - Ariel Azzario Rachmandha; Renny Husniati (ITB AAS INDONESIA, 2022)
This study is a quantitative study with the aim of knowing and proving the effect of job satisfaction, career development, and work environment on turnover intention at PT XYZ. The population in this study were employees of PT XYZ with staff positions, then the number of samples was determined as many as 88 respondents using the purposive method and convenience sampling and data were collected by google form. The analytical technique used in this research is using inferential analysis using SmartPLS 3.3.5. In this study, the results of the R Square value is 0.641 or 64.1%, then the results of hypothesis testing in this study are as follows, (1) there is a positive and significant effect between job satisfaction on turnover intention which has an effect of 0.144, (2) there is a positive and significant influence between career development on turnover intention which has an effect of 0.542, and (3) there is a positive and significant effect between the work environment on turnover intention which has an influence of 0.231, and (4) the variables of job satisfaction, career development, and work environment simultaneously affect turnover intention